Transitional justice and corporate accountability from below: deploying Archimedes' lever - Payne, Leigh A. (Cambridge University Press, 2020)
"Bruno Tesch was tried, found guilty, and executed for his company's production and sale of the Zyklon B gas used in Nazi Germany's extermination camps. Tesch was not alone. More than 300 economic actors faced prosecution for crimes against humanity during the Holocaust. This book examines those trials and subsequent judicial and non-judicial (truth commission) efforts up to the present to hold economic actors accountable for complicity in gross violations of human rights during armed conflict and authoritarian rule. It probes what these accountability efforts are, why they take place, and when, where , and how they unfold. It also explores obstacles blocking accountability efforts, particularly business veto power and weak international law. The book uses an original oneof- its-kind Corporate Accountability and Transitional Justice database to develop its argument. It claims that the accountability processes underway around the world constitute "accountability from below," a kind of Archimedes' Lever in which the right tools in weak hands can lift weighty international human rights"-- Provided by publisher